2021
DOI: 10.3389/fphys.2021.764702
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Endothelial Activation and Dysfunction Induced by Antiphospholipid Antibodies Among Groups of Patients With Thrombotic, Refractory, and Non-refractory Antiphospholipid Syndrome

Abstract: Antiphospholipid syndrome (APS) is an autoimmune disorder characterized by pregnancy morbidity or thrombosis and persistent antiphospholipid antibodies (aPL) that bind to the endothelium and induce endothelial activation, which is evidenced by the expression of adhesion molecules and the production of reactive oxygen species (ROS) and subsequent endothelial dysfunction marked by a decrease in the synthesis and release of nitric oxide (NO). These endothelial alterations are the key components for the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The role of NO is also the inhibition of platelet adhesion and aggregation, leukocyte adhesion and migration, and smooth muscle proliferation. Therefore, the impairment of NO production leads towards a prothrombotic phenotype [ 30 ]. In PAPS patients, aCL antibody titers inversely correlate with urinary NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…The role of NO is also the inhibition of platelet adhesion and aggregation, leukocyte adhesion and migration, and smooth muscle proliferation. Therefore, the impairment of NO production leads towards a prothrombotic phenotype [ 30 ]. In PAPS patients, aCL antibody titers inversely correlate with urinary NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…Another collection of recent studies evaluated endothelial activation and dysfunction in cultured endothelial cells exposed to various serum factors from APS patients [33 ▪▪ ,34,35]. One study found that IgG isolated from patients with different disease phenotypes (primary APS, secondary APS, APS refractory to treatment, and obstetric APS) resulted in the differential expression of markers related to endothelial activation and dysfunction [33 ▪▪ ]. For example, polyclonal IgG from refractory APS patients increased the production of microparticles, reactive oxygen species (ROS), and endothelin-1 while reducing nitric oxide production.…”
Section: Endothelial Activation and Injurymentioning
confidence: 99%
“…These changes lead to a reduction in vascular integrity, an increase in the expression of adhesion molecules and cytokine production propagating inflammation, and an enhancement of human leukocyte antigen (HLA) molecules [ 31 ]. The increase of adhesion molecules, including ICAM-1 (intercellular adhesion molecule-1), VCAM-1 (vascular cell adhesion molecule-1), and E-Selectin, facilitates the adherence of leukocytes on the endothelium and their subsequent transmigration to the sub-endothelium [ 32 , 33 ]. In addition, the production of cytokines, including interleukins and tumor necrosis factors, regulates the immune response [ 31 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of adhesion molecules, including ICAM-1 (intercellular adhesion molecule-1), VCAM-1 (vascular cell adhesion molecule-1), and E-Selectin, facilitates the adherence of leukocytes on the endothelium and their subsequent transmigration to the sub-endothelium [ 32 , 33 ]. In addition, the production of cytokines, including interleukins and tumor necrosis factors, regulates the immune response [ 31 , 33 ]. The above enhances the risk of thrombocytic events [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation